Cold War on CNN, Part 20: Soldiers of God 1975-1988 (United Kingdom : Jeremy Isaacs Productions, 1998)
For centuries, nations had tried to conquer Afghanistan. None succeeded. But the Cold War -- and an Afghan civil war -- would bring a terrible toll of death and destruction to the people of this traditionally Islamic land.
Keywords: United Kingdom